Analytical Enzymatic Saccharification of Lignocellulosic Biomass for Conversion to Biofuels and Bio-Based Chemicals - Madhavi Latha Gandla; Carlos Martín; Leif J. Jönsson (Energies, 2018)
Lignocellulosic feedstocks are an important resource for biorefining of renewables to bio-based fuels, chemicals, and materials. Relevant feedstocks include energy crops, residues from agriculture and forestry, and agro-industrial and forest-industrial residues. The feedstocks differ with respect to their recalcitrance to bioconversion through pretreatment and enzymatic saccharification, which will produce sugars that can be further converted to advanced biofuels and other products through microbial fermentation processes. In analytical enzymatic saccharification, the susceptibility of lignocellulosic samples to pretreatment and enzymatic saccharification is assessed in analytical scale using high-throughput or semi-automated techniques. This type of analysis is particularly relevant for screening of large collections of natural or transgenic varieties of plants that are dedicated to production of biofuels or other bio-based chemicals. In combination with studies of plant physiology and cell wall chemistry, analytical enzymatic saccharification can provide information about the fundamental reasons behind lignocellulose recalcitrance as well as about the potential of collections of plants or different fractions of plants for industrial biorefining. This review is focused on techniques used by researchers for screening the susceptibility of plants to pretreatment and enzymatic saccharification, and advantages and disadvantages that are associated with different approaches.